"ELIMINATION OF CULTURE BASED DISCRIMINATION AGAINST WOMEN IN INDONESIA: AN ASSESSMENT OF THE IMPLEMENTATION OF STATE PARTIES’ OBLIGATIONS UNDER ARTICLE 5(A) OF THE WOMEN’S CONVENTION" - Tuslian, Widya Naseva (Indonesia Law Review, 2019)
The notion of cultural relativism has always been a fundamental challenge to upholding human rights values, especially regarding gender mainstreaming and the equality of both sexes. In this sense, there is a view that cross-cultural moral values are not acceptable given thecultural traits that produce their own modes of thinking and ideology. It is thus understandable that Article 5(a) of the Women’s Convention (i.e.,The Convention on the Elimination of all Forms of Discrimination Against Women), which is the only provision in international law that seeks to modify cultures that prejudice women, will deal with constant hurdles in countries like Indonesia that firmly embrace cultural values. This is true even though a signal of commitment has been shown by ratification because the signal itself makes not reservation to the obligations stipulated therein. However, these commitments remain highly questionable as discriminatory laws remain in force across the country from the national to the local level and new discriminatory regulations continue to be issued. The Committee of Elimination of Discrimination Against Women (CEDAW) has reminded Indonesia at some occasion that cultural and religious values must not undermine the universality of women’s rights. Nevertheless, up until now, the authorities have always failed to create a clear timeframe for revision of laws that institutionalize negative stereotypes against women. Taking this perspective into account, this paper will explore the reasons for and indicators of Indonesia’s failure to implement Article 5(a) to modify cultural values and stereotypes against women in its legal system and instruments. In doing so, this paper will also dig deeper into Indonesia’s barriers to implementing its state obligations under this article.